2008
DOI: 10.1007/s12046-008-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

The extrinsic influence of carbon fibre reinforced plastic laminates to strengthen steel structures

Abstract: The intrinsic advantages of strengthening the steel-based structures by the use of fibre reinforced plastic (FRP) material have not yet been fully exploited. In this paper, a succinct overview of recent studies made to enhance the strength of steel beams using FRP laminates is presented. The results presented and discussed in this paper were obtained by closely studying the behaviour of steel beams strengthened with carbon FRP material. An attempt is made to succinctly summarise the findings for two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…In other research, Selvaraj and Madhavan (2017) investigated C channel steel beams rehabilitated with CFRP sheet and found an improvement in failure modes (from lateral torsional buckling to yielding) and flexural moment capacity of the beams. Patnaik et al, (2008) studied flexural and shear strengthening of steel girders with CFRP plates. They showed that by using CFRP plates attached to the web of the girders, shear strength of the steel girders could be increased.…”
Section: © Ascementioning
confidence: 99%
“…In other research, Selvaraj and Madhavan (2017) investigated C channel steel beams rehabilitated with CFRP sheet and found an improvement in failure modes (from lateral torsional buckling to yielding) and flexural moment capacity of the beams. Patnaik et al, (2008) studied flexural and shear strengthening of steel girders with CFRP plates. They showed that by using CFRP plates attached to the web of the girders, shear strength of the steel girders could be increased.…”
Section: © Ascementioning
confidence: 99%
“…Some researchers have demonstrated different techniques for strengthening of steel webs subjected to shear by CFRP. Patnaik et al (2008) [11] has published results of an analytical and experimental program focused on shear strengthening of steel built-up I-beams. In this research three steel beams were designed to fail in shear.…”
Section: Introductionmentioning
confidence: 99%
“…Most scientific research on the topic of FRP reinforcements and adhesives have been developed in the last five years. In most cases, carbon fibers were applied in the composition of FRP reinforcement [4][5][6][7][8][9][10], while some studies considered glass fibers [4,5,[10][11][12][13] or basalt fibers [14]. Furthermore, the FRP material as reinforcement was applied in different manners, as profiled shape ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…b) Ordered fibers and in situ application of the polymer matrix[8].c) FRP fabrics[6]. d) FRP laminated strips[10].| Reinforcement by stiffening the web surface using FRP and structural adhesives…”
mentioning
confidence: 99%